Majority-of-the-minority shareholder votes and investment efficiency - Cao, Ning; McGuinness, Paul B.; Xi, Chao (Journal of Corporate Finance, 2024)
In an environment where concentrated share ownership is the norm, we ask whether Majority-of-the-Minority (MoM) votes curb controlling shareholder overreach and investment inefficiency. We consider MoM votes on controller-based related party transactions in China. Such votes give minority parties potential veto power. We report strong association between shareholder disapprovals on controller-based investment related MoM proposals and the underlying entity's investment plans. This association is robust to a battery of tests, including assessment of pre-vote consultation between minority and controlling shareholders and an exogenous regulatory shock. We also report increased likelihood of informal securities enforcements in the year following MoM shareholder disapproval.